Закон семи: роман / Татьяна Полякова - Полякова Татьяна Викторовна (Авантюрный детектив, 2006)
Экземпляры: ЦБ (20140305) / Инвентарный номер: 45620 / Цена: 100.00 / Авт.знак: П 54 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6